Prognostic impact of adding Coronary Calcium Score to European SCORE2 in an asymptomatic Portuguese population. (3rd October 2022) - Temtem, M; Mendonca, M I; Serrao, M; Santos, M; Sa, D; Soares, C; Sousa, A C; Henriques, E; Rodrigues, M; Freitas, S; Borges, S; Ornelas, I; et al.
Abstract: Introduction: The new European SCORE2 estimates the combined risk of fatal and non-fatal cardiovascular (CV) events, in contrast with SCORE's use for CV mortality only. Although controversial, several studies point out that Coronary Artery Calcification (CAC) scoring could improve CV risk stratification in primary prevention. Purpose: Assess the impact of including CAC score to the new SCORE2 in MACE prediction and CV risk stratification in an asymptomatic Portuguese population. Methods: The new SCORE2 was calculated in a population-based cohort of 1, 014 individuals (mean age 58.6±8.5 years) without known CV disease and diabetes. Population was stratified into three SCORE2 risk categories (low-, moderate- and high-risk). According to the Hoff's nomogram, CAC score was categorized into: low CAC (0≤CAC<100 or P<50); moderate CAC (100≤CAC<400 or P50–75) and high or severe CAC (CAC≥400 or P>75). Kaplan-Meier survival curves were estimated and a multivariate regression analysis predicted the MACE risk for both scores. C-statistic methodology evaluated the ability of CAC when added to the SCORE2 model in MACE prediction. Results: Kaplan-Meier curves showed that the highest categories of both scores presented a worst survival. Cox regression analysis showed that the highest categories of both CAC and SCORE2 remained in the equation with an increased MACE risk (HR) of 3.69 (p=0.008) and 9.87 (p=0.005), respectively, when compared with the lowest categories. C-statistic demonstrated that the predictive value for MACE increased from 0.668 (SCORE2 model) to 0.787 when CAC was included (p=0.012), showing a better predictive and discriminative capacity for MACE. Conclusions: Our results highlight the importance of adding CAC score to SCORE2 in primary prevention to improve cardiovascular risk stratification and MACE risk prediction. Larger prospective multicenter cohorts with longer follow-up should reproduce and validate these findings. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): SESARAM EPERAM